The Missing Link in Budget Models of Nonprofit Institutions: Two Practical Dutch Applications - Verheyen, Piet (Management Science, 1998)
The Dutch government, health insurance associations, and research boards allocate budgets to nonprofit institutions (hospitals, universities), based on general indicators (inhabitants, admissions, or students). With these budgets, the top management of each institution (the principal) allocates the funds, using general indicators to distribute the money further down to the base. At the base of the nonprofit institutions, the professionals (the agents) perform a spectrum of specific tasks. Tension around the budgetting process exists between top management and professionals. This paper resolves the tension along the research lines of Burton and Obel (1995) by measuring in money terms the specific tasks of the professionals of universities and hospitals at the base, and by reconsidering the theoretical background of the internal budget system. The study also develops the missing link in an integral external and internal budget system by integrating the managerial and professional decisions or the input-output decisions in one approach.